Isolation of Polyhydroxysterols from a Species of Sarcophyton of the Indian Ocean - Chandra Sekhar, V.; Bheemasankara Rao, Ch.; Venkata Rao, D.; Sarvani, B.; Lakshmi, D.K.M. (Asian Journal of Chemistry, 2016)
A new trihydroxysterol, (24S)-4α,24-dimethylcholestane-3β,6α,25-triol (1) was isolated from a soft coral Sarcophyton sp. collected from the coasts of Gulf of Mannar, Indian Ocean together with four known polyhydroxy sterols 3, 4, 5 and 6, that was earlier reported as its pentaacetate. The structures were derived by spectral data.